2019
DOI: 10.1136/oemed-2019-105797
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of prognostic factors for work participation in patients with sciatica

Abstract: Sciatica impacts on the ability to work and may lead to a reduced return to work. This study reviewed and summarised prognostic factors of work participation in patients who received conservative or surgical treatment for clinically diagnosed sciatica. We searched MEDLINE, CINAHL, EMBASE and PsycINFO until January 2018. Cohort studies, using a measure of work participation as outcome, were included. Two independent reviewers performed study inclusion and used the Quality In Prognosis Studies tool for risk of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 36 publications
1
35
0
Order By: Relevance
“…This seems a factor related to ‘fear avoidance beliefs’, which is included as an important prognostic factor for participation in patients with sciatica. 12 Steenstra et al found insufficient evidence for fear avoidance beliefs in later phases for patients with low back pain. 16 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This seems a factor related to ‘fear avoidance beliefs’, which is included as an important prognostic factor for participation in patients with sciatica. 12 Steenstra et al found insufficient evidence for fear avoidance beliefs in later phases for patients with low back pain. 16 …”
Section: Discussionmentioning
confidence: 99%
“… 17 Pain coping has also been identified as a prognostic factor for participation in patients with sciatica. 12 In our research, the population included patients with mental disorders, which might be the reason for the pain variables to be non-significant. Hence, patients with mental disorders often do not consistently identify their complaints as pain related.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 12 , 13 ] Although surgery benefits for patients suffering from persistent sciatica, the efficiency of surgery can not last for a long time and the expenditure could not be afforded. [ 14 ] Traditional Chinese medicine, especially acupuncture therapy as a safe and efficient treatment is popular among patients. [ 15 ]…”
Section: Introductionmentioning
confidence: 99%